Experimental investigation of wear-hardness trade-off mapping for quenched HSS tools under different quenching media and austenitizing temperatures - Razali, Razali; Setyawan, Reinaldi Teguh; Yendra, Alfazan Yendra (Politeknik Negeri Lhokseumawe, 2026)
This study investigates the wear-hardness trade-off of quenched AISI M2 High-Speed Steel (HSS) cutting tools subjected to three austenitizing temperatures (800, 900, and 1000°C) and three quenching media (salt water, Bromus oil, and SAE 20 oil), without subsequent tempering treatment. A factorial dataset consisting of three austenitizing temperatures (800, 900, and 1000°C) and three quenching media (salt water, Bromus oil, and SAE 20 oil) was analyzed under fixed turning parameters (n=300 rpm, f=0.19 mm/rev, a_p=1.5 mm). Tool performance was evaluated using flank wear (VB) and Rockwell hardness (HRC), with five hardness readings per condition to quantify repeatability. The results show a dominant temperature effect: VB decreases monotonically as austenitizing temperature increases, while hardness rises markedly at 1000°C, forming a favorable region with simultaneously low wear and high hardness. The best combined performance was obtained at 1000°C with SAE 20 oil, achieving VB = 0.066 mm and HRC ≈ 82.8. A desirability-style composite index D, derived from normalized VB (smaller-is-better) and HRC (larger-is-better), produced decision and rank maps that consistently identified the 1000°C region as the optimal operating window, with oil quenching preferred when high-temperature austenitizing is feasible. Hardness repeatability metrics further indicated that the 1000°C conditions exhibit the lowest scatter, strengthening their practical robustness. The proposed mapping framework offers a compact, reproducible approach to visualize the wear–hardness trade-off and to rank heat-treatment conditions using existing experimental data.